EFEKTIVITAS KELEMBAGAAN DAN ALIRAN INFORMASI UNTUK OPTIMALISASI PENGELOLAAN LAHAN SURUTAN BENDUNGAN GAJAH MUNGKUR DI KABUPATEN WONOGIRI - Bekti Wahyu Utami; Marcelinus Molo; Emi Widiyanti (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2011)
This study was designed to explore effectiveness of institusions and optimizing the flow of information for land management in drawdown area Gajah Mungkur. The research was conducted by surveying over 63 farmers and land drawdown area with focus groups discussion and interviewed supervisors at Gajah Mungkur dam. In terms of effectiveness of institutions and the flow of information, based on the achievement of drawdown conservation, the study team come to the following conclusions. The directives, in this case reflecting the institutions, have not fully effective anyway. Some farmers did not comply with the directives for better soil management of the drawdown area. Of the surveyed farmers, the soil conservation of 14,1% of them belonged to the bad or very bad achievers. Those findings lead to the following potential recommendations: to make the institutions and the information flow is more effective it is  suggested to improve organizing the farmers at the grassroot level. The farmers might be better organized into group of farmers and such groups are organized into higher order of group, such as Gabungan Kelompok Tani;  Re-organizing the farmers may also lead to a shift from the existing top-down relation to a partnership relationship among the dam security members with the renters. Keywords: institutional, information flow, drawdown area